Representing and querying validity time in RDF and OWL: A logic-based approach. - Motik, B (2012)
RDF(S) and OWL 2 currently support only static ontologies. In practice, however, the truth of statements often changes with time, and Semantic Web applications often need to represent such changes and reason about them. In this paper we present a logic-based approach for representing validity time in RDF and OWL. Unlike the existing proposals, our approach is applicable to entailment relations that are not deterministic, such as the Direct Semantics or the RDF-Based Semantics of OWL 2. We also extend SPARQL to temporal RDF graphs and present a query evaluation algorithm. Finally, we present an optimization of our algorithm that is applicable to entailment relations characterized by a set of deterministic rules, such RDF(S) and OWL 2 RL/RDF entailment. © 2010 Springer-Verlag.